The spread of alien species along the touristic routes of the Słowiński National Park - Krzyżanowska, Anastazja; Tomczyk, Przemysław Piotr; Pruszkowska-Przybylska, Paulina; Zielińska, Katarzyna Maria (Acta Universitatis Lodziensis. Folia Biologica et Oecologica, 2018)
Touristic routes have a great meaning for the spread of alien species through the protected areas like national parks. The aim of the study was to assess the spread of the chosen species along the different kinds of touristic routes of the Słowiński National Park and asphalt roads lying in the direct vicinity of the Park, in its protective zone. The presence of 108 localities of eight alien species were recorded (Padus serotina, Quercus rubra, Acer negundo, Robinia pseudoacacia from woody species and Conyza canadensis, Impatiens parviflora, Juncus tenuis and Oxalis fontana from herbaceous plants). The localities of the woody plants were found in areas where they were formerly deliberately planted or near routes leading to such areas. All of the analysed woody plants can be the source of ecological threat and should be actively removed. Interestingly, regarding herbaceous plants, the species which according to literature are not a threat to untransformed habitats – Juncus tenuis and Oxalis fontana – were noted quite commonly. Their populations should be monitored. The populations of Impatiens parviflora, classified to the IV class of invasiveness and Conyza canadensis, which can invade sand dunes, should be destroyed as soon as possible till they occupy small areas.